2007
DOI: 10.1159/000098834
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Terminal Syringomyelia in Association with Pediatric Tethered Cord Syndrome

Abstract: An association between terminal syringomyelia (TS) and tethered cord syndrome (TCS) has been recognized. The clinical significance of TS and the need for concurrent treatment is not known. Thirty-four patients with TCS undergoing surgery for tethered cord release were evaluated for the incidence of TS. The clinical and radiological response to untethering with and without syrinx drainage was assessed. The group incidence of TS was 29.4%. There were no significant differences in the sex, age, underlying patholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…The traditional diagnosis of TCS has required radiographic evidence of a short, thick or fatty FT and a lowlying CMD with its tip positioned at or below the lower endplate of L 2 [23,48,59,65,74,78,82]. The syndrome is associated with an increased incidence of terminal thoracic syringomyelia [7,12,22]. …”
Section: Discussionmentioning
confidence: 99%
“…The traditional diagnosis of TCS has required radiographic evidence of a short, thick or fatty FT and a lowlying CMD with its tip positioned at or below the lower endplate of L 2 [23,48,59,65,74,78,82]. The syndrome is associated with an increased incidence of terminal thoracic syringomyelia [7,12,22]. …”
Section: Discussionmentioning
confidence: 99%
“…In terminal syringomyelia associated with tethered cord, as in our case, spinal dysraphism or intramedullary tumor, the cyst may show regression or even disappear after surgical treatment of the underlying pathologies (2,10,12,15). Although there is a risk of recurrence in cases of the syringomyelia treated without shunting, this risk is known to be low after the definite treatment of the underlying pathology, and restoring the normal CSF flow (2,10,12,15). In the present case, the authors preferred only to untether the cord, thus achieving definite treatment of the underlying pathology and expecting a high rate of success in treating the syringomyelia (2,10,12,15), which may avoid the need for syringosubarachnoid shunting and the insertion of foreign materials.…”
Section: Discussionmentioning
confidence: 69%
“…Although the optimum surgical procedure is still controversial, syringosubarachnoid shunt placement seems to be an effective treatment in symptomatic cases (3,4,10). In terminal syringomyelia associated with tethered cord, as in our case, spinal dysraphism or intramedullary tumor, the cyst may show regression or even disappear after surgical treatment of the underlying pathologies (2,10,12,15). Although there is a risk of recurrence in cases of the syringomyelia treated without shunting, this risk is known to be low after the definite treatment of the underlying pathology, and restoring the normal CSF flow (2,10,12,15).…”
Section: Discussionmentioning
confidence: 75%
“…This would be concordant with previous pediatric TC studies suggesting the absence of correlation between level of termination of the conus medullaris and clinical symptoms, 6,31 or between a postoperative decrease in the size of a syrinx and clinical symptom resolution. 3,18 This study demonstrated that half of the surgically treated children had a conus medullaris below the level of L-2 and this finding had no significant association with height outcome. While TC is classically associated with a low-lying conus medullaris, other studies have noted that TC can occur in the absence of a low-positioned conus medullaris.…”
Section: Discussionmentioning
confidence: 72%